Intestinal helminths of bats in the States of Nayarit and Veracruz, Mexico, with redescription of Bidigiticauda vivipara Chitwood - Moguel-Chin, Wilson I.; Digiani, María Celina; G., M. Cristina Macswiney; Ortega, Jorge; Ospina-Garcés, Sandra M.; García-Prieto, Luis; Canché-Pool, Elsy B.; Robles, María Del Rosario; Ávila-López, Mariana B.; Chan-Casanova, Anyela Jackelin; Panti-May, Jesús Alonso (Zootaxa, 2025)
Although surveys on bat parasites in the Americas have been conducted, information on helminths remains limited. In Mexican states such as Nayarit and Veracruz only 1 and 8 helminth species have been reported in bats, respectively. In this study, we provide new helminthological records for bats using morphological techniques. Also, the 28S rRNA gene of specimens from several helminth taxa was successfully amplified and sequenced. To confirm the identification at the generic level, and in some cases at the specific level, and the genealogical relationships of the parasites, we performed the phylogenetic analyses using the new 28S rRNA sequences. From March to May 2022, 16 bats of 10 species are captured and examined for helminths. Three bat species of two families, two Vespertillionidae (Bauerus dubiaquercus and Rhogeessa parvula) and one Phyllostomidae (Glossophaga mutica), are parasitized by helminths. Seven helminth taxa are morphologically identified: the trematodes Urotrema scabridum and Anenterotrema cf. hastati, the cestodes Vampirolepis macroti, Vampirolepis sp. (1), and Vampirolepis sp. (2), and the nematodes Bidigiticauda vivipara and Capillariidae gen. sp. The first helminthological records for R. parvula and B. dubiaquercus and the 28S rRNA gene data of B. vivipara, V. macroti, and Vampirolepis spp. are provided. The findings of the present study increase the number of helminth taxa recorded in Mexican bats from 78 to 79, as well as the number of bat species with helminthological records from 35 to 37.